Mustawiyat al-Dirasah al-Arabiyah Li Aghrad Ammah: al-Marhalah al-Ibtidaiyah Wa al-Mutawasithah Wa al-Muqaddimah Mustawiyat al-Ada' al-Mukhtalifah Fi Mumarisah al-Lughah Bima Fiha Min Jawanib Ma'rifiyah Au Wajdaniyah Au Nafs Harkiyah - Yaqin, Muhammad Ainul (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This research discusses the Arab study levels for general purposes and from the perspective of cognitive and emotional intelligence. This research is phenomenal in Indonesia and is one of the qualitative approach of the genus phenomenon. That the levels are divided into three sections I, which is special for the new learners who participate in the programs of teaching the Arabic language, like any language of teaching to non-native speakers without knowledge of the language or familiarity with them. The conversation at this level is limited to the memorization of these students models of the correct Arab conversation and its topics are usually specific. There is no way to diversify the attitudes of the student. Level Two the highest level of precedent The conversation at this level usually revolves around broader topics, more complex issues, and more abstract consensus. At this level, the conversation revolves around topics and ideas. Students study in specific texts, from which they draw ideas woven around them, issues they discuss, and simple problems that exchange views. Level Three This represents the highest level of conversation in the teaching of Arabic as a second language. At this level, learners are expected to practice conversation in the sense that we have taken for conversation in that it is an automatic free discussion on a given subject and two individuals conversing. The student at this level usually has extensive linguistic experience and the ability to use syntax correctly. Understanding different versions of one expression and putting each of them in the right place.